MENINGKATKAN KREATIVITAS BELAJAR DENGAN PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) PADA SISWA KELAS V SDN 5 TALLUNGLIPU KABUPATEN TORAJA UTARA - Weryanti Laen Langi' (Institute Agama Islam Al-Qolam Malang, 2023)
This study discusses Increasing Student Creativity in the Thematic subject of fifth grade students at SDN 5 Tallunglipu, North Toraja Regency with the Application of Project Based Learning Models. The purpose of this study was to increase the learning creativity of fifth grade students by implementing the Project-Based Learning Model in fifth grade at SDN 5 Tallunglipu, North Toraja Regency. The approach used is Classroom Action Research and consists of 2 cycles. Each cycle consists of 3 stages, namely planning, action and observation, reflection. The subjects of this study were fifth grade students at SDN 5 Tallunglipu, North Toraja Regency, for the 2022/2023 academic year, consisting of 15 male students and 16 female students. The focus of this research is the teacher's ability to apply or prohibit a Thematic material and students see learning creativity in understanding the material taught in the learning process. The research results obtained are that the application of a project-based learning model can increase student learning creativity in Thematic Theme 5 Ecosystem lessons, both in terms of teacher teaching, student learning activities and student learning creativity. This can be seen from the students' learning creativity, where in the first cycle it shows that maximum learning outcomes have not been achieved or the classical completeness of students' learning creativity only reaches 53.82% and learning incompleteness reaches 46.18%. In cycle II there was an increase because it was in the very creative category, the completeness of learning creativity had reached 86.81%, while the incompleteness reached 13.19%. From the results of the study it was stated that through the Application of Project-Based Learning Models Student Learning Creativity in thematic learning of class V SDN 5 Tallunglipu North Toraja district increased.